The Role Of School Leadership In Internalizing Religious Moderation Values In Multicultural Contexts - Muh Ibnu Sholeh (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study investigates the role of school leadership in internalizing religious moderation values within multicultural educational contexts through a library research approach. The study addresses three main aspects: conceptual leadership roles, implementation strategies, and their impact on student development and institutional sustainability. Data were collected from scholarly books, peer-reviewed journal articles, and policy documents related to educational leadership and multicultural education. The analysis employed thematic synthesis and interpretive review to identify patterns across the literature. The findings indicate that school leadership functions as a central mechanism in embedding moderation values through vision alignment, ethical role modeling, and participatory practices. Moderation values are integrated into curriculum, school culture, and extracurricular activities, creating consistent experiences that foster tolerance, empathy, and critical awareness among students. Leadership also influences school climate, collaboration, and adaptive capacity, contributing to institutional resilience. The study concludes that effective school leadership provides a coherent framework for strengthening religious moderation through alignment of vision, policy, and educational practice in diverse contexts.